Evolution of the BBAA Component of Bread Wheat during Its History at the Allohexaploid Level . Issue 7 (2nd July 2014) - Zhang, Huakun; Zhu, Bo; Qi, Bao; Gou, Xiaowan; Dong, Yuzhu; Xu, Chunming; Zhang, Bangjiao; Huang, Wei; Liu, Chang; Wang, Xutong; Yang, Chunwu; Zhou, Hao; et al.
Abstract : The extracted tetraploid wheat (ETW) containing the BBAA subgenomes of hexaploid bread wheat has a stabilized karyotype but anomalous phenotypes. Genome-wide comparisons between ETW and natural tetraploid wheat revealed a large number of differentially expressed genes in ETW; these changes showed early occurrence and evolutionary persistence during bread wheat evolution. Abstract: Subgenome integrity in bread wheat ( Triticum aestivum ; BBAADD) makes possible the extraction of its BBAA component to restitute a novel plant type. The availability of such a ploidy-reversed wheat (extracted tetraploid wheat [ETW ]) provides a unique opportunity to address whether and to what extent the BBAA component of bread wheat has been modified in phenotype, karyotype, and gene expression during its evolutionary history at the allohexaploid level. We report here that ETW was anomalous in multiple phenotypic traits but maintained a stable karyotype. Microarray-based transcriptome profiling identified a large number of differentially expressed genes between ETW and natural tetraploid wheat ( Triticum turgidum ), and the ETW -downregulated genes were enriched for distinct Gene Ontology categories. Quantitative RT-PCR analysis showed that gene expression differences between ETW and a set of diverse durum wheat ( T. turgidum subsp durum ) cultivars were distinct from those characterizing tetraploid cultivars per se. Pyrosequencing revealed that the expression alterations may occur to either only one or both of the B and A homoeolog transcripts in ETW . A majority of the genes showed additive expression in a resynthesized allohexaploid wheat. Analysis of a synthetic allohexaploid wheat and diverse bread wheat cultivars revealed the rapid occurrence of expression changes to the BBAA subgenomes subsequent to allohexaploidization and their evolutionary persistence.